Efectividad del enalapril comparado con alfametildopa en el control de presión arterial en puérperas mediatas con preeclampsia severa, atendidas en el Hospital Belen de Trujillo, 2021 - 2022. - Ramírez Delerna, Ernesto Arturo (2021)
Preeclampsia (PE) is a syndrome of unknown cause that affects only human pregnancy, and is characterized by arterial hypertension (AHT) and/or target organ damage during delivery and/or immediate puerperium; in most cases it follows an asymptomatic course and is only discovered when routine blood pressure measurements are performed and sometimes hypertensive disorders are not limited to the gestational period and can extend, debut or conclude in the puerperium, with the first 24h and the first week postpartum being considered the critical period. However, there are currently insufficient data regarding that the choice depends on experience and familiarity with the drug, knowing the adverse effects.